SIZE AND SHAPE MATTER: THE MODIFIABLE AREAL UNIT PROBLEM IN NEIGHBORHOOD EFFECTS RESEARCH. - Onubogu, Carl. (2017)
Abstract: This paper serves as an exploration of the Modifiable Areal Unit Problem (MAUP) for professionals and researchers investigating neighborhood effects. It begins with a literature review that explores the MAUP and its relevance to an understanding neighborhood effects. Next it compares four different approaches to defining neighborhood boundaries by testing five variables aggregated to those boundaries. The results show wide variation in aggregated values, in support of claims that the MAUP exists in neighborhood effects research. The results also demonstrate that researchers need to be cognizant of the impact of the MAUP on analysis of neighborhood effects.; Thesis (M.A.)--Tufts University, 2013.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Barbara Parmenter.; Committee: Laurie Goldman.; Keywords: Urban planning, and Geographic information science and geodesy.